Economic Cost-Benefit Analysis of Nerve Implanted into Muscle versus Targeted Muscle Reinnervation versus Regenerative Peripheral Nerve Interface, for Treatment of the Painful Neuroma - Zamore, Zachary; Yesantharao, Pooja S.; Aravind, Pathik; Dellon, A. Lee (Journal of Reconstructive Microsurgery, 2024)
Background This study investigated the relative cost utility of three techniques for the management of symptomatic neuromas after neuroma excision: (1) implantation of nerve into muscle, (2) targeted muscle reinnervation (TMR), and (3) regenerative peripheral nerve interface (RPNI).Methods The costs associated with each procedure were determined using Common Procedural Terminology codes in combination with data from the Centers for Medicaid and Medicare Services Physician and Facility 2020 Fee Schedules. The relative utility of the three procedures investigated was determined using changes in Patient-Reported Outcomes Measurement Information System (PROMIS) and Numeric Rating Scale (NRS) pain scores as reported per procedure. The relative utility of each procedure was reported in terms of quality-adjusted life years (QALYs), as is standard in the literature.Results The least expensive option for the surgical treatment of painful neuromas was nerve implantation into an adjacent muscle. In contrast, for the treatment of four neuromas, as is common postamputation, TMR without a microscope was found to cost $50,061.55 per QALY gained, TMR with a microscope was found to cost $51,996.80 per QALY gained, and RPNI was found to cost $14,069.28 per QALY gained. While RPNI was more expensive than nerve implantation into muscle, it was still below the standard willingness-to-pay threshold of $50,000 per QALY, while TMR was not.Conclusion Evaluation of costs and utilities associated with the various surgical options for the management of painful neuromas suggest that nerve implantation into muscle is the least expensive option with the best improvement in QALY, while demonstrating comparable outcomes to TMR and RPNI with regard to pain symptoms.
Keywords: neuroma; TMR; RPNI; cost utility